LEVEL OF SATISFACTION OF BIRTHING MOTHER AT JAMPERSAL PROGRAMÂ AT REGION WORK PUSKESMAS BLOOTO MOJOKERTO - Basuki, Duwi; Mujayanti, Titin (Jurnal Keperawatan Bina Sehat, 2011)
Some Midwives seem less respect or being negative towards the provision of medicines and services both to the MOM who uses maternity Jampersal. This resulted in the birthing Mother was not satisfied with the use of Jampersal services.. The purpose of this research is to know the level of satisfaction of the birthing mother of jampersal program in the region work Puskesmas Blooto Mojokerto. The design of this research is descriptive. The population of this research that all mothers maternity program that uses jampersal in the region work Puskesmas Blooto Mojokerto 37 mothers maternity by using guarantees delivery. Study on the sample taken with purposive sampling technique as much as 32 respondents. Research of variable levels of satisfaction the maternity Mother on jampersal program. Data collected by questionnaire instrument and processed in coding, editing, tabulating and scoring, then presented in the form of a frequency distribution table. The results showed that the majority of respondents were satisfied with the service jampersal as many as 17 respondents (53.1%) and a small percentage are not satisfied with the service received as many as 15 (46,9%) respondents. This indicates that most of the resonden were satisfied with the service given by health workers in Clinics Blooto because the officer friendly in talk, deft in doing action and responsiveness if needed by the patient. The satisfaction felt by the patient jampersal programs, most patients feel satisfied so that health workers can be expected to enhance the capabilities and skills in providing service delivery satisfaction so they can deliver better services on patients and patients satisfaction in receiving services can be fulfilled properly.Key Words : Satisfaction, Jampersal